PERAN GURU DALAM MENINGKATKAN MOTIVASI HASIL BELAJAR SISWA DALAM PEMBELAJARAN FIQIH DI MTsN 14 HULU SUNGAI TENGAH - Ubaidillah Ubaidillah (CV. ADIBA AISHA AMIRA, 2023)
Motivation is the overall physical driving force within students that causes learning activities, ensures the continuity of learning activities and gives direction and learning activities from achieving a goal. Motivation is characterized by reactions to achieve goals, motivated individuals carry out responses that aim to reduce tension caused by changes in energy within themselves, each response is a step towards a goal. According to the Indonesian dictionary, the result is something that exists (happens) by a job, is successful. Meanwhile, according to R.Gagne, results are seen as internal abilities that belong to the person and the person does something. Meanwhile, the etymological understanding of learning is learning to learn from the word